SEMANTIC PECULIARITIES OF ARGUMENTATION "LANGUAGE GAME": CONTEXT LOGICAL ANALYSIS - Комаха, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The paper examines argumentation in the system of logical analysis, which aims to its linguistic forms. It is shown that the logic of science forms the analysis of language, which includes certain statements in a language system with clearly specified essential characteristics. Attention is focused on the structure of thought; clarity is determined by the exact formulation thoughts in language. This is the meaning of evidence and argumentation to analyze language.